RANCANG BANGUN PEMUTUS ALIRAN LISTRIK SISTEM TEGANGAN RENDAH BERBASIS INTERNET OF THINGS (IoT) PADA DAERAH BANJIR - Ajeng Bening Kusumaningyas (Jurnal Poli-Teknologi, 2022)
Floods are a frequent disaster and the danger from electricity is something that needs to be considered during a flood. Design the low-voltage system power breaker based on the Internet of Things (IoT) in this flooded area is a detection device that is connected to the internet, so it can detect if there is a water level rising remotely using a smartphone. This tool works by using the Ultrasonic sensor HC-SR04 to detect the water level that has risen and a microcontroller to process the data, disconnect the MCCB and display it in the smartphone system remotely. The Ultrasonic HC-SR04 sensor can measure a distance of 2cm to 450 cm from the sensor. To make this system, it requires a microcontroller communication, namely the MCU Node which is equipped with a Wi-Fi ESP 8266 module as a master which functions to receive data with a distance of centimeters and a button to disconnect the MCCB to the Blynk application on the smartphone. Water level data and data graphs can be viewed directly on the Blynk interface and the data recap can be sent to a spreadsheet. However, there is some delay when the sensor works because the process of sending data to the spreadsheet only takes a few seconds and does not interfere with the performance of the Internet of Things (IoT) based low-voltage system power breaker in flooded areas. Key words : Blynk, ESP 8266, Water Level